Theoretical Study of the Effect of Pentagon/Heptagon Defects on the Electronic Behaviour of Coiled Carbon Nanotubes: A Review - (:unkn) unknown (University Of Eloued جامعة الوادي, 2020)
Coiled carbon nanotube (CCNT) structure is the result of the periodic insertion of the pentagon and heptagon pairs (defect) into the carbon hexagonal network of the nanotube causing positively and negatively curved surface. Based on theoretical studies, regular coiled nanotubes exhibit exceptional electronic, mechanical, electrical, optic and magnetic properties due to the combination of their peculiar helical morphology and the fascinating properties of nanotubes. Although coiled carbon nanotubes provide attractive features, there is little both theoretical and experimental research. In the present work, we attempted to clarify essential aspect of the electronic behaviour of CCNTs and summarize results obtained until now.
Intervention
Keywords: coiled carbon nanotube; pentagon/heptagon pairs (defect); carbon hexagonal network; structure; electronic properties